An Analysis of Generic Structure on Recount Text Written by Tenth Grade Students of SMA 8 Kota Jambi in the Academic Years 2017/2018 - Ayu Firmala Sari, Wennyta, Yanti Ismiyati (JELT: Journal of English Language Teaching, 2018)
AbstractThis research is aimed to find out how is generic structure on recount text written by tenth grade students of SMA 8 Jambi 2017/2018. The kind of research is qualitative research. The data collected from class X.1 as 32 students. Method of collecting data used in this research is test. Researcher found that students most of the students wrote good recount text based on generic structure and some of them still have to increase their knowledge about generic structure on recount text. The class average of students’ test result of the test is 20,12. The highest and the lowest scoreof generic structure of 26 and 8 from 32 students. The average of students’ test result of each generic structure consist on orientation is 7,71, events 5,87, and re-orientation 6,53. The highest percentage of students’ knowledge is orientation 38,35% and the lowest percentage of students’ knowledge is events 29,19%. It can be conclude that students more understand about orientation than events and re-orientation.Keywords: Analysis, Generic Structure, RecountText.